Designing and standardizing the proficiency test for knot tying, as well as the open knot tying test, for scout troops in high schools. - Riyadh Nuri Abbas; Muhammad Abdul Razzaq; Riyadh Alsaeed (University of Basrah, 2023)
The practice of the scout movement in our country is concentrated within the scope of schools, as it is an important part of education sports. So, Scout teams are formed within the school, which contribute to the various activities of the movement, including camping and practicing artistic and cultural activities and sports. In order to reach scout teams with good capabilities, as well as for the purpose of standing on the level of performance of the selection of students participating in scout teams, special tests for scouting skills must be conducted through designing and codifying tests that give real values ​​and the real level for scouts, it is within their competence in the field of scout movement, tests and measurement, and after reviewing theoretical studies, the researchers have come to the fact that there are no tests and measurements that give an evaluation of these skills. The researchers wanted to study this problem by designing special tests to evaluate the performance of some scouting skills for scout teams in high school